Relationship between eating disorders and self-image assessment in female health university students at a private college in the Federal District (Research, Society and Development, 2024)
Introduction: Eating disorders are disturbances caused by changes in eating and psychological behavior. Their origin is multifactorial, but strongly influenced by social pressure and the search to fit into a pattern. Objective: To analyze the relationship between eating disorders and self-image assessment in female university students in the health area at a private college in the Federal District. Methodology: A cross-sectional, observational study was carried out with 50 female university students from the health area of a private institution in Brasília. Female health students enrolled in nutrition, psychology, nursing, biomedicine, physiotherapy, and medicine were invited to participate in the study. Males and incomplete questionnaires were excluded. The students completed a sociodemographic form, including age, physical activity, weight, and height, and a self-completed questionnaire validated in Portuguese, the Eating Attitudes Test (EAT-26), and the Kakeshita Scale. The analysis was done using SPSS software (version 25), with a chi-square test to assess risk behavior for eating disorders. Results: 50% were from the nutrition course, with an average age of 21.9 years, 66% were eutrophic and 66% said they were active. When asked about putting on weight, 88% said they were afraid. Of these, 62% were eutrophic. In addition, 88% were worried about wanting to be thin. When it came to assessing the risk of developing eating disorders, 64% were at risk (p=0.048). Conclusion: The public with the highest scores for eating disorders and poor self-image were university nutrition students, and for body dissatisfaction, they were eutrophic.